Proactive biomanagement and its relationship to professional moral courage among doctors and nurses working in COVID-19 isolation hospitals - Al-Sabab, Azhar Mohammed Majeed; Jasim, Dia Nemir (Al-Adab Journal, 2022)
Managing proactive vitality can be described as individual goal-oriented behavior aimed at managing physical and mental energy to promote optimal performance at work, and moral courage is defined as the voluntary willingness to stand up for one's moral beliefs and act in accordance with them despite barriers that may prevent the ability to proceed toward action It is correct, since medical personnel (doctors - nurses) in light of the spread of the Corona epidemic are exposed to exhaustion and fatigue, as well as, there are professional pressures related to the ethics and charter of the profession that they swore to, so the researchers chose to be the sample of the research medical personnel (doctors - nurses). The study aimed to identify the extent of their possession of Managing proactive vitality in the context of their medical work, and the extent of their professional moral courage. The research problem was summarized by the following question: Is there a relationship between Managing proactive vitality and professional moral courage among medical staff (doctors - nurses). The research sample consisted of (213) doctors and nurses working in health isolation hospitals, and the researchers built a Managing proactive vitality scale based on the definition of Op den Kamp et al., 2018, and the scale items were in its final form (33) a paragraph. As well as by building a scale of professional moral courage based on the definition of Sekerka (Sekerka et al. 2007), and the paragraphs of the scale in its final form were (40) items, and honesty and stability were extracted, so the two scales became ready to be applied to the research sample, and after applying and processing the data, The results showed that the research sample of doctors and nurses was distinguished by a high level of Managing proactive vitality, as well as a high level of, professional moral courage, and that there is a positive and significant relationship between Managing proactive vitality and professional moral courage.